Challenges and Strategies for Community Nurses in Tackling Mental Health Issues - Priyono, Habib (Oshada, 2025)
Mental health problems are an increasing global challenge, especially at the community level. Community nurses play a crucial role in identifying, preventing and treating mental health problems in the community. However, they face various barriers, such as limited resources, social stigma, and lack of specialized training in managing mental health disorders. This study aims to identify the challenges community nurses face in addressing mental health problems and formulate strategies that can be implemented to improve the effectiveness of their role. This study used a descriptive qualitative approach to explore the challenges and strategies relevant for community nurses in addressing mental health issues. The results showed various challenges faced by community nurses in addressing mental health issues in the community, including social stigma, limited resources, lack of specialized training, cultural barriers, and suboptimal coordination of services. These challenges have a significant impact on the ability of community nurses to provide effective care that is responsive to patient needs. However, innovative solutions can be implemented to address these issues, such as stigma reduction through community education, cross-cultural training, strengthening nurses' capacity through continuous training, and utilizing digital technology to support referral systems and cross-sector communication. The implications of this study emphasize the importance of policy support in strengthening the role of community nurses in addressing mental health. With the right strategies, community nurses can be more effective in providing interventions and services that support community mental health.